Strategi Pembelajaran Dan Ketrampilan Sosial Terhadap Perolehan Hasil Belajar: Learning Strategies and Social Skills in Relation to Academic Achievement - Moh. Sutomo (Fenomena, 2017)
The ineffectiveness of social studies learning in junior high schools is often caused by teacher-centered approaches that neglect students' social potential. This study aims to examine the effect of learning strategies and social skills on learning outcomes. Using a 2x2 factorial quasi-experimental design with a nonequivalent control group design, the study involved 111 eighth-grade students from public junior high schools in Lumajang Regency. Data were collected through social skills questionnaires and learning outcome documents focusing on comprehension and analytical skills, then analyzed using MANOVA with SPSS 20.0. The findings reveal that (1) there is a significant difference in learning outcomes between students taught using the jigsaw cooperative learning strategy and those taught using traditional methods, and (2) there is an interaction effect between learning strategy and social skills on student learning outcomes. The study recommends that teachers adopt cooperative learning strategies, particularly jigsaw, to optimize both academic achievement and social skill development. Ketidakefektifan pembelajaran IPS di SMP sering disebabkan oleh pendekatan yang berpusat pada guru dan mengabaikan potensi sosial siswa. Penelitian ini bertujuan menguji pengaruh strategi pembelajaran dan keterampilan sosial terhadap hasil belajar. Menggunakan desain eksperimen semu faktorial 2x2 dengan rancangan nonequivalent control group design, penelitian melibatkan 111 siswa kelas VIII dari SMP Negeri di Kabupaten Lumajang. Data dikumpulkan melalui angket keterampilan sosial dan dokumen hasil belajar (kemampuan memahami dan menganalisis), lalu dianalisis dengan MANOVA berbantuan SPSS 20.0. Hasil penelitian menunjukkan bahwa (1) ada perbedaan signifikan hasil belajar antara kelompok yang dibelajarkan dengan strategi jigsaw dibandingkan strategi tradisional, dan (2) ada pengaruh interaksi antara strategi pembelajaran dan keterampilan sosial terhadap hasil belajar siswa. Penelitian ini merekomendasikan guru untuk menggunakan strategi pembelajaran kooperatif tipe jigsaw guna mengoptimalkan pencapaian akademik sekaligus pengembangan keterampilan sosial.